(untitled) - Prof. Dr. Marion Büttgen; Prof. Dr. Andreas Eggert; Prof. Dr. Heiner Evanschitzky; Prof. Dr. Christiane Hipp; Prof. Dr. Jens Hogreve; Prof. Dr. Joachim Hüffmeier; Prof. Dr. Helmut Krcmar; Prof. Dr. Martin Matzner (SMR - Journal of Service Management Research, 2023)
SMR is a platform for the academic dialog between service researchs from different economic disciplines. It offers critical depictions of the newest developments in the central areas of service research. Thereby SMR dedicates itself particularly to interdisciplinary research agendas. For more information for authors and subscribers, see rsw.beck.de/zeitschriften/smr.